FORMULASI DAN UJI STABILITAS SEDIAAN ANTISEPTIK FOOT SPRAY GEL MINYAK ATSIRI SERAI WANGI (Cymbopogon nardus (L.) Randle) - Kurnia Listiyanti; Diah Ramadhani (Fakultas Farmasi Universitas 17 Agustus 1945 Jakarta, 2021)
The citronella plant is a plant that comes from the Poaceae family which has the main content of citronellal, citronellol and geraniol. Lemongrass essential oil is an essential oil that is often used as raw material for perfumes, antiseptics, cosmetics, medicines, food and beverage flavors and the aroma of kretek cigarettes. This research was conducted to determine the formulation and stability test antiseptic preparations lemongrass essential oil foot spray gel. This study carried out a spray gel formulation with various amounts of lemongrass essential oil made in four formulas, namely F1, F2, F3 and F4, the evaluation carried out in this study was organoleptic examination, homogeneity, pH, viscosity, dispersibility, adhesion spreadability, spray pattern & weight per spray, dry time, cycling test and hedonic. The antiseptic foot spray gel of lemongrass essential oil shows that the higher concentration of citronella essential oil contained in the formula, the more liquid preparation is, resulting in a decrease in the viscosity value and shows a little flow of sticky dispersion, whereas in the evaluation of the spreadability, weight per spray and Dry time showed an increase in each formula, meanwhile the stability evaluation using the cycling test method at F1, F2, F3 and F4 gave stable results except on organoleptic examinations in the aroma criteria that decreased the intensity of aromatic odors at F2, F3 and F4 at 6th cycle.